2008
DOI: 10.1042/bst0360813
|View full text |Cite
|
Sign up to set email alerts
|

How autophagy is related to programmed cell death during the development of the nervous system

Abstract: Programmed cell death, together with proliferation and differentiation, is an essential process during the development of the nervous system. During neurogenesis, neurons and glia are generated in large numbers and, subsequently, they die in a process that depends on trophic signalling that refines the cytoarchitecture and connectivity of the nervous system. In addition, programmed cell death also affects proliferating neuroepithelial cells and recently differentiated neuroblasts. Autophagy is a lysosomal degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 44 publications
2
26
0
3
Order By: Relevance
“…Cell death associated with neurogenesis in the DT region of the E4 and E5 retina seems to require autophagy (reviewed in ref. 17), whereas morphogenetic cell death in the ON region, as well as later neurotrophic cell death, does not.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Cell death associated with neurogenesis in the DT region of the E4 and E5 retina seems to require autophagy (reviewed in ref. 17), whereas morphogenetic cell death in the ON region, as well as later neurotrophic cell death, does not.…”
Section: Resultsmentioning
confidence: 91%
“…13,14 Recent studies have revealed a homeostatic role of autophagy with respect to apoptosis and the clearance of dead cells associated, at least, with cavitation in mouse embryoid bodies and chick retinal development. [15][16][17] In these studies, the genetic inhibition of autophagy, by using knockout mice of Atg genes, as well as its pharmacological inhibition, by 3-methyl-adenine (3-MA), prevented PS presentation and the subsequent phagocytosis of apoptotic bodies.…”
Section: Introductionmentioning
confidence: 99%
“…LysoTracker has also been a useful tool for assessing autophagy [23][24][25][26] and in response to serum starvation, differentiated ES cells display a marked increase in the number of LysoTracker staining puncta (compare Figure 2D with 2A). This likely indicates an increase in the formation of autophagolysosomes and lysosomes in response to decreased nutrient availability (as has been shown in other contexts using LysoTracker 24,25 ).…”
Section: Discussionmentioning
confidence: 99%
“…ATP in turn delivers energy for the removal of apoptotic cells through engulfment and subsequent degradation. In the mature CNS, mechanical or biochemical insults of neurons are often accompanied by autophagy, which is thought to promote regenerative events or cell destruction, depending on the spatial-temporal context (Boya et al, 2008).…”
Section: Discussionmentioning
confidence: 99%